Hubungan Aksi Boikot K-Popers Terhadap Minat Beli Brand Grup Kpop - Briliani, Khoirunnisa; Ulil Albab; Ruslaini (CV. ULIL ALBAB CORP, 2024)
The Relationship between K-Popers Boycott Action and Kpop Group Brand Purchase Intention. This study aims to examine the relationship between boycott actions taken by K-pop fans (K-popers). A purposive sampling procedure was used to select 95 respondents for this quantitative study, which focused on K-pop fans aged between 15 and 25 years old. The independent variable is Boycott Action and the dependent variable is Purchase Intention. Measured through survey completion. Using SPSS V.29 for Windows, the data analysis method utilized non-parametric statistics and simple regression tests. This can explain the relevance value of the data based on the findings of the simple linear regression test. The Boycott Action variable affects the Purchase Intention variable, according to the coefficient table which produces a significance value of 0.001 <0.05. The correlation or relationship value (R) of 50% from the output results in a coefficient of determination (R squere) value of 25.6%, The results of this study indicate that boycott action has an impact on consumer intention to buy products from companies that partner with K-pop artists.